Correlation of clinical, biochemical and radiological characteristics with histopathology of ovarian masses: hospital based descriptive study - Laul, Poonam; Miglani, Urvashi; Srivastava, Atima; Sood, Neelam; Miglani, Sanjeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ovarian cancer is an important cause of morbidity and mortality in the middle aged women. A systematic study of all ovarian tumours encountered in a large institute over a period of years is more likely to produce a significant amount of useful data regarding the clinical manifestations, the incidence of various types of ovarian tumours and the type of treatment offered. In this study we correlate various clinical presentations, ultrasound features, and various tumour marker levels with histopathology of ovarian masses. Methods: The study was conducted in the department of obstetrics and gynaecology in collaboration with department of radiology and pathology and lab medicine, Deen Dayal Upadhyay hospital from April 2015 to December 2016. Results: In the present study, 97 ovarian masses have been operated out of total 708 gynaecological surgeries in the obstetrics and gynaecology department of Deen Dayal Upadhyay hospital over the stipulated period. Prevalence of ovarian masses was 13.7%. Most of the ovarian masses were prevalent in the reproductive age group i.e. 21-40 years of age group in the present study though malignant masses were commonest in post-menopausal age group in the present study. 2 out 11 malignant ovarian masses were in the age group of 10-20 years which were dysgerminoma and immature teratoma respectively. Intra-operative findings like presence of mural nodule, haemorrhage and necrosis, ascites, papillary excrescences and omental caking were also found to have strong correlation with malignancy. Conclusions: A detailed preoperative workup and a simple tool loke RMI can differentiate between benign and malignant masses pre-operatively especially in post-menopausal women.